ANTIPLATELET AGENTS IN THE TREATMENT AND SECONDARY PREVENTION OF ISCHEMIC STROKE (REVIEW OF LITERATURE) - E. Y. Kitaeva; V. V. Shprakh (Acta Biomedica Scientifica, 2017)
The literature review provides basic information about cerebral stroke as one of the leading medical and socio-economic problems that caused high levels of mortality and morbidity from stroke, unfavorable disability index. This fact confirms the need for the introduction of efficient preventive measures among the healthy population and among patients with a stroke. The basic principles of secondary prevention, as well as the primary, are minimizing the risk factors and drug therapy. Antiplatelet therapy is a key point in the treatment and secondary prevention in patients with an ischemic stroke. On the basis of evidence-based data with the characteristics of antiplatelet agents, included in clinical guidelines and standards for the treatment of patients with ischemic stroke. Patients with ischemic stroke, if there are no contraindications for the appointment of antiplatelet agents, are prescribed antiplatelet agents from the first day (aspirin, clopidogrel and others). Patients usually have to take these drugs constantly (for life). The drug of choice in patients with intolerance, contraindications or complications of therapy with acetylsalicylic acid, as well as in patients with a stroke and diabetes, peripheral arterial disease, coronary syndrome, is clopidogrel. The literature review shows the basic principles of selection and prescription of antiplatelet agents tactics to ischemic stroke patients at different stages of the disease. A balanced, pharmacotherapeutically safe approach to the use of antiplatelet agents is very important. It raises the question of the need to apply the principles of personalized medicine in patients with a stroke, including the prescription of antiplatelet agents.